2021
DOI: 10.1038/s41598-021-00149-1
|View full text |Cite
|
Sign up to set email alerts
|

Multi-drug resistance and high mortality associated with community-acquired bloodstream infections in children in conflict-affected northwest Nigeria

Abstract: Pediatric community-acquired bloodstream infections (CA-BSIs) in sub Saharan African humanitarian contexts are rarely documented. Effective treatment of these infections is additionally complicated by increasing rates of antimicrobial resistance. We describe the findings from epidemiological and microbiological surveillance implemented in pediatric patients with suspected CA-BSIs presenting for care at a secondary hospital in the conflict affected area of Zamfara state, Nigeria. Any child (> 2 months of age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…This result demonstrates that hospital pediatric patients are more affected by drug-resistant bacterial bloodstream infections. 75 Usage of Indwelling medical devices has exposure to multidrug resistance bloodstream infection. History of incubation has exposure to MDR bacterial infection.…”
Section: Discussionmentioning
confidence: 99%
“…This result demonstrates that hospital pediatric patients are more affected by drug-resistant bacterial bloodstream infections. 75 Usage of Indwelling medical devices has exposure to multidrug resistance bloodstream infection. History of incubation has exposure to MDR bacterial infection.…”
Section: Discussionmentioning
confidence: 99%
“…In 2019, S. aureus was amongst the top three pathogens responsible for global deaths associated with antimicrobial resistance (AMR), with methicillin-resistant S. aureus (MRSA) causing more than 100,000 annual deaths [ 3 ]. While SAB epidemiology is well described in high-income countries [ 2 , 4 ], data from low-income countries, particularly in sub-Saharan Africa, remain scarce [ 5 , 6 ]. This study aims to describe the burden, epidemiological trends and clinical presentation of community-acquired SAB among children aged < 5 years in southern Mozambique, between 2001 and 2019.…”
Section: Introductionmentioning
confidence: 99%
“…One of the laboratories included in our study reported yeast as the most commonly isolated microorganism from blood cultures. Indeed, yeasts are among the microorganisms isolated from bloodstream infections, but they are a relatively rare finding ( 4 , 14 , 23 , 24 ). It can therefore be assumed that, given the very low number of positive blood cultures in the laboratory in question, contamination and misidentification distorted the results.…”
Section: Discussionmentioning
confidence: 99%